Barriers and Facilitators to Parental Help-Seeking for Young Children With Developmental Delays: A Qualitative Investigation. (June 2020) - Marshall, Jennifer; Raffaele Mendez, Linda M.; Singleton, Destiny L.
This study examined influences, factors, and processes associated with parental recognition and response to developmental concerns through interviews and focus groups with six Spanish- and 17 English-speaking parents of children aged 2 weeks to 4.5 years with developmental concerns. Results revealed that social support, perceptions of perceived threat (the child's susceptibility to developmental problems and potential severity of the issue), evaluation of the benefits and barriers of seeking help, self-efficacy, and referral coordination influenced parents' recognition and response to developmental concerns. Experiences and paths to services varied greatly, illustrating the lack of consistency within service systems. Understanding these influences in identification and intervention is the first step in addressing how to better support parents and their children.